Defects of cohesin loader lead to bone dysplasia associated with transcriptional disturbance. Issue 12 (25th June 2021) - Gu, Weihuai; Wang, Lihong; Gu, Renjie; Ouyang, Huiya; Bao, Baicheng; Zheng, Liwei; Xu, Baoshan
Abstract: Cohesin loader nipped‐B‐like protein (Nipbl) is increasingly recognized for its important role in development and cancer. Cornelia de Lange Syndrome (CdLS), mostly caused by heterozygous mutations of Nipbl, is an autosomal dominant disease characterized by multiorgan malformations. However, the regulatory role and underlying mechanism of Nipbl in skeletal development remain largely elusive. In this study, we constructed a Nipbl‐a Cas9‐knockout (KO) zebrafish, which displayed severe retardation of global growth and skeletal development. Deficiency of Nipbl remarkably compromised cell growth and survival, and osteogenic differentiation of mammalian osteoblast precursors. Furthermore, Nipbl depletion impaired the cell cycle process, and caused DNA damage accumulation and cellular senescence. In addition, nucleolar fibrillarin expression, global rRNA biogenesis, and protein translation were defective in the Nipbl‐depleted osteoblast precursors. Interestingly, an integrated stress response inhibitor (ISRIB), partially rescued Nipbl depletion‐induced cellular defects in proliferation and apoptosis, osteogenesis, and nucleolar function. Simultaneously, we performed transcriptome analysis of Nipbl deficiency on human neural crest cells and mouse embryonic fibroblasts in combination with Nipbl ChIP‐Seq. We found that Nipbl deficiency caused thousands of differentially expressed genes including some important genes in bone and cartilage development. In conclusion, Nipbl deficiency compromised skeleton development through impairing osteoblast precursor cell proliferation and survival, and osteogenic differentiation, and also disturbing the expression of some osteogenesis‐regulatory genes. Our study elucidated that Nipbl played a pivotal role in skeleton development, and supported the fact that treatment of ISRIB may provide an early intervention strategy to alleviate the bone dysplasia of CdLS. Abstract : Nipbl deficiency triggers ISR accompanied by dysregulated ribosome biogenesis and reduced protein translation, nucleolar aberration, defective growth, and differentiation of embryonic osteoblast precursors. Such cellular stress causes poor cell viability, apoptosis, increasing DNA damage (γH2ax and 8‐oxog), and cell senescence (senescence‐associated galactosidase activity), respectively. Osteogenic differentiation was also perturbed by Nipbl haploinsufficiency, associated with reduced alkaline phosphatase (ALP) activity and mineralization capacity, and misregulation of osteogenic genes (Alp, Col1a1, Runx2, and Osterix) and some osteogenesis‐regulatory signaling (ERK/MAPK, EIF2 signaling, RhoA signaling, and Rho Family GTPases). Excitedly, ISRIB, a first bona fide ISR inhibitor, partially alleviated some defects in osteogenic differentiation and growth retardation upon Nipbl haploinsufficiency.